2022
DOI: 10.1097/fjc.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Induced Acute Kidney Injury in Diabetic Patients and SGLT-2 Inhibitors: A Preventive Opportunity or Promoting Element?

Abstract: Contrast-induced acute kidney injury (CI-AKI) is a serious complication in patients undergoing diagnostic or therapeutic procedures that require contrast use and negatively affects the long-term outcomes. Patients with type 2 diabetes mellitus (DM), particularly those who have already developed diabetic nephropathy (DN), are more susceptible to contrast-induced renal damage. Indeed, contrast media amplify some pathological molecular and cellular pathways already in place in the DN setting. In recent years, sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…The most important finding obtained as a result of this study: The risk of nephropathy due to the use of contrast media after CAG and/or PCI procedures in diabetic patients with SGLT2 inhibitor in the treatment regimen was found to be significantly lower than in the patient group who did not use SGLT2 inhibitors. This is one of the pioneering studies in the literature showing that SGLT2 inhibitors may have a potential benefit in reducing or preventing the development of CIN and is, to our knowledge, the first study with an isolated NST-ACS patient population [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important finding obtained as a result of this study: The risk of nephropathy due to the use of contrast media after CAG and/or PCI procedures in diabetic patients with SGLT2 inhibitor in the treatment regimen was found to be significantly lower than in the patient group who did not use SGLT2 inhibitors. This is one of the pioneering studies in the literature showing that SGLT2 inhibitors may have a potential benefit in reducing or preventing the development of CIN and is, to our knowledge, the first study with an isolated NST-ACS patient population [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for inhibiting sodium–hydrogen exchanger 3 (NHE3), an antiporter located on the epithelial cells of the proximal tube that imports sodium ions, simultaneously ejecting hydrogen ions in the proximal tubule lumen. NHE3 inhibition increases natriuresis and diuresis [ 32 , 33 , 34 ].…”
Section: Physiological Mechanisms Of Incretinsmentioning
confidence: 99%
“…This study is designed to evaluate the cumulative efficacy, safety, and tolerability of dual therapy, including finerenone and empagliflozin in people with CKD and diabetes [ 79 ]. Considering the well-known protective effects of sodium–glucose transporter 2 inhibitors (SGLT2i) on the cardiovascular system [ 80 ] and renal functions [ 9 ], dual therapy with finerenone and SGLT2i could provide an additive effect in order to slow the disease progression and provide long-term benefits for patients with diabetes and CKD [ 79 ].…”
Section: Finerenone: From Bench To Bedsidementioning
confidence: 99%
“…However, the optimal titration of this combination is often hampered by suboptimal creatinine levels, as only few studies included patients with an estimated glomerular filtration rate (eGFR) < 30 mL/min [ 7 ]. Similarly, the use of sodium–glucose transporter 2 inhibitors (SGLT2i) for the treatment of heart failure also offers renal protection [ 8 , 9 ]. A recent study in patients with advanced CKD (eGFR 25–45 mL/min) showed that empagliflozin was associated with a reduced risk of renal progression or cardiovascular death compared to a placebo (hazard ratio, 0.72; 95% confidence interval [CI], 0.64–0.82; p < 0.001) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%